Laboratory evolution and physiological analysis of Saccharomyces cerevisiae strains dependent on sucrose uptake via the Phaseolus vulgaris Suf1 transporter. Issue 12 (15th October 2018) - Marques, Wesley Leoricy; van der Woude, Lara Ninon; Luttik, Marijke A.H.; van den Broek, Marcel; Nijenhuis, Janine Margriet; Pronk, Jack T.; van Maris, Antonius J.A.; Mans, Robert; Gombert, Andreas K.
Abstract: Knowledge on the genetic factors important for the efficient expression of plant transporters in yeast is still very limited. Phaseolus vulgaris sucrose facilitator 1 ( Pv Suf1), a presumable uniporter, was an essential component in a previously published strategy aimed at increasing ATP yield in Saccharomyces cerevisiae . However, attempts to construct yeast strains in which sucrose metabolism was dependent on PvSUF1 led to slow sucrose uptake. Here, PvSUF1‐ dependent S. cerevisiae strains were evolved for faster growth. Of five independently evolved strains, two showed an approximately twofold higher anaerobic growth rate on sucrose than the parental strain (μ = 0.19 h −1 and μ = 0.08 h −1, respectively). All five mutants displayed sucrose‐induced proton uptake (13–50 μmol H + (g biomass) −1 min −1 ). Their ATP yield from sucrose dissimilation, as estimated from biomass yields in anaerobic chemostat cultures, was the same as that of a congenic strain expressing the native sucrose symporter Mal11p. Four out of six observed amino acid substitutions encoded by evolved PvSUF1 alleles removed or introduced a cysteine residue and may be involved in transporter folding and/or oligomerization. Expression of one of the evolved PvSUF1 alleles ( PvSUF1 I209F C265F G326C ) in an unevolved strain enabled it to grow on sucrose at the same rate (0.19 h −1 ) as the corresponding evolved strain. This study shows how laboratory evolution may improve sucrose uptake in yeast via heterologous plant transporters, highlights the importance of cysteine residues for their efficient expression, and warrants reinvestigation of Pv Suf1's transport mechanism.